The Development of Democratic Politics through the Process of Local Governance: The Development of Democratic Politics through the Process of Local Governance - Suebmuengsai, Kumsee; Ardwichai, Wedsuwan; Yanamethi, Phramaha Thainoi; Thinsandee, Theeraphat (RATANABUTH JOURNAL, 2025)
This academic article aims to study the role of local governance processes in promoting and developing democratic politics at the local level. The analysis is conducted through the dimensions of administrative structure, citizen participation, and mechanisms of checks and balances. The findings reveal that local administrative organizations serve as a crucial mechanism for decentralizing power from the central government to local areas. This decentralization enables citizens to directly engage in political decision-making processes, express their opinions, and participate in a wide range of public activities—such as electing local leaders, co-developing local development plans, contributing opinions through public forums, and being involved in mechanisms that monitor and balance the executive’s use of power. For democratic development through local governance to be truly effective, it requires fostering an informed and active citizenry with positive attitudes toward democracy. Simultaneously, it necessitates improving local administrative systems to be transparent, accountable, and inclusive—creating spaces where citizens can play a genuine role in shaping the direction of their own communities. Such conditions will help lay a strong foundation for sustainable democracy in Thai society. However, the study also identifies several limitations that hinder democratic development at the local level. These include a lack of knowledge and understanding among citizens about their civic roles and responsibilities, a deeply rooted patronage-based political culture, symbolic or superficial participation, and resource constraints faced by local administrative organizations.